2022
DOI: 10.3389/fcvm.2022.1081098
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidosis: What does pathology offer? The evolving field of tissue biopsy

Abstract: Since the mid-nineteenth century pathology has followed the convoluted story of amyloidosis, recognized its morphology in tissues and made identification possible using specific staining. Since then, pathology studies have made a significant contribution and advanced knowledge of the disease, so providing valuable information on the pathophysiology of amyloid aggregation and opening the way to clinical studies and non-invasive diagnostic techniques. As amyloidosis is a heterogeneous disease with various organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 122 publications
0
6
0
2
Order By: Relevance
“…Возможно применение метода сцинтиграфии с меченным йодом сывороточным P-компонентом. При подозрении на AL-А рекомендуется также производить трепанобиопсию костного мозга с подсчетом плазматических клеток и окраской пунктата на амилоид 6 .…”
Section: Clinical Experienceunclassified
“…Возможно применение метода сцинтиграфии с меченным йодом сывороточным P-компонентом. При подозрении на AL-А рекомендуется также производить трепанобиопсию костного мозга с подсчетом плазматических клеток и окраской пунктата на амилоид 6 .…”
Section: Clinical Experienceunclassified
“…1 Diagnosis is established through histopathologic evaluation revealing extracellular eosinophilic, hyaline, acellular, amorphous, and homogeneous deposits with a characteristic staining pattern seen with Congo Red and polarizing microscopy. [1][2][3] Although early recognition is crucial for optimal patient management, it is often underdiagnosed. 4,5 Subtype nomenclature is based on the protein from which the amyloid is derived and the structure of the abnormal protein deposited.…”
mentioning
confidence: 99%
“…In addition, Congo Red-negative cases have been documented, adding to the difficulty in establishing a diagnosis. 3,14 Improved recognition of histopathological features associated with amyloid deposition could improve recognition and early diagnosis. This retrospective observational study aimed to characterize the most commonly observed deposition patterns in the GIT and evaluate key quality metrics, including misinterpretations, to improve recognition and provide insight for accurate diagnosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations